(untitled) (Global Journal of Computer Science and Technology, 2013)
Cost estimation is one of the most challenging tasks in project management. It is to accurately estimate needed resources and required schedules for software development projects. The software estimation process includes estimating the size of the software product to be produced, estimating the effort required, developing preliminary project schedules, and finally, estimating overall cost of the project. Nearly one-third projects over run their budget and late delivered and two-thirds of all major projects substantially over run their original estimates. Effort is a function of size. For estimating effort first we face sizing problem. In direct approach size is measured in lines of code (LOC). In indirect approach, size is represented as Function Points (FP). In this paper we use both approach with different technique.